Coronary artery bypass grafting in a 14-year-old boy with compound heterozygous LDLR familial hypercholesterolemia: a case report - Zhu, Ke; Zhang, Fuqiang; Wang, Jin; Li, Chunjing (Frontiers in Pediatrics, 2025)
Familial hypercholesterolemia (FH), particularly homozygous or compound heterozygous forms, predisposes individuals to premature cardiovascular disease due to severely elevated low-density lipoprotein cholesterol (LDL-C). This case report describes a 14-year-old boy with compound heterozygous pathogenic variants in the LDLR gene, diagnosed with FH with a strong family history of hypercholesterolemia. Despite early initiation of statins, the patient developed progressive angina pectoris. Coronary angiography revealed critical stenosis in the left main arteries, necessitating urgent coronary artery bypass grafting (CABG). Arterial as opposed to venous conduit selection in pediatric homozygous familial hypercholesterolemia warrants explicit rationale. In the postoperative stage, LDL-C levels remained elevated but were managed with adjunctive therapies, including PCSK9 inhibitor. Genetic testing confirmed compound heterozygosity, underscoring the aggressive nature of LDLR dysfunction. This case highlights the challenges of managing severe FH in pediatric patients, emphasizing the importance of early genetic diagnosis, multimodal lipid-lowering therapy, and timely surgical intervention to prevent life-threatening complications. It also reinforces the necessity of lifelong monitoring and developing novel therapeutic strategies to treat compound heterozygous FH cases. This report contributes to the limited literature on CABG in pediatric FH, advocating for a multidisciplinary approach to optimize outcomes in this high-risk population.